(K, Na)NbO3 lead-free piezoceramics prepared by microwave sintering and solvothermal powder synthesis. (15th September 2022) - Li, Haitao; Hao, Yijin; Lin, Zihan; He, Xinyun; Cai, Jiaqi; Gong, Xintai; Gu, Yongjun; Zhang, Rui; Cheng, Haoyan; Zhang, Boping
Abstract: Low temperature and short processing time are favorable for fabricating (K, Na)NbO3 (KNN) lead-free piezoelectric ceramics with a drawback of easy alkali metal volatilization during the powder synthesis and sintering processes. This study revealed that microwave sintering (MS) in addition to microwave solvothermal synthesis (MSS) of powder can lead to short-time fabrication of KNN ceramics with high density and fine grains. It was found that when the concentration of KOH/NaOH exceeds 1 M, KNN powder with single perovskite structure can be synthesized successfully by MSS method, which can be densified by MS to a high relative density close to 97% at 1050 °C even using 2/9 shorter time than conventional sintering (CS) at the same temperature. Importantly, the MSed KNN ceramics show better piezoelectric and ferroelectric properties than CSed counterparts. Without any dopants, the piezoelectric coefficient ( d 33 ) of the MSed pure KNN ceramics is 132 pC/N, and the remnant polarization ( P r ) is 26.3 μC/cm 2 . The results show that the MS method is a promising method for preparing KNN-based ceramics. Highlights: Microwave solvothermal method avoids errors in composition of synthesized powder. . Microwave sintering can shorten the sintering time to 30 min. Electrical properties of d 33  = 132 pC/N and P r  = 26.3 μC/cm 2 are achieved.